1995
DOI: 10.1029/95jc00222
|View full text |Cite
|
Sign up to set email alerts
|

Particulate and dissolved spectral absorption on the continental shelf of the southeastern United States

Abstract: Visible absorption spectra of particulate and dissolved materials were characterized on the continental shelf off the southeastern United States (the South Atlantic Bight), emphasizing cross-shelf and seasonal variability. A coastal front separates turbid coastal waters from clearer midshelf waters. Spatial and seasonal patterns were evident in absorption coefficients for phytoplankton, detritus, and colored dissolved organic matter (CDOM); spectral shape parameters for CDOM and detritus; and phytoplankton chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
43
2
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 46 publications
24
43
2
1
Order By: Relevance
“…Advection and diffusion by the background flow further modulates the distribution of CDOM absorption. There may also be an additional in-water source of CDOM associated with phytoplankton [Twardowski, 1998], which we did not observe in our data, though it may contribute to the different a a -s relationship observed farther downstream at the South Atlantic Bight [Nelson and Guarda, 1995]. This sink/source layout results in a spatial distribution of CDOM, which is decreasing away from shore (with increase in salinity) and increasing with depth at the shelf (also with increase in salinity).…”
Section: Resultscontrasting
confidence: 53%
“…Advection and diffusion by the background flow further modulates the distribution of CDOM absorption. There may also be an additional in-water source of CDOM associated with phytoplankton [Twardowski, 1998], which we did not observe in our data, though it may contribute to the different a a -s relationship observed farther downstream at the South Atlantic Bight [Nelson and Guarda, 1995]. This sink/source layout results in a spatial distribution of CDOM, which is decreasing away from shore (with increase in salinity) and increasing with depth at the shelf (also with increase in salinity).…”
Section: Resultscontrasting
confidence: 53%
“…Figure 4 shows the two parameters plotted against each other and the apparent inverse relationship. A similar relationship was also seen between a and S. Inverse * 375 relationships between a 375 and S in marine waters have been reported before in the literature (Green 1992;Blough et al 1993;Nelson and Guarda 1995;Vodacek et al 1997; among others). However, care must be taken when studying the behavior of S in natural waters, as it is highly sensitive to the wavelength range over which it is estimated.…”
Section: ϫ64a375supporting
confidence: 62%
“…As a consequence of its fresh water origin and conservative behavior, CDOM absorption in coastal seas has been previously observed to be inversely correlated with salinity in the same way, and therefore has been considered a good indicator of salinity in various regions (e.g. Jerlov, 1968;Nelson and Guarda, 1995;Boss et al, 2001;Binding and Bowers, 2003;Kwalczuk et al, 2005;Moon et al, 2006;Guo et al, 2007;Sasaki et al, 2008). Findings from the above relationships of salinity and a CDOM (λ) revealed that salinity seemed to be better correlated with a CDOM at 400 nm than a CDOM at other longer wavelengths, and therefore a CDOM at 400 nm could be used as a proxy for salinity in this region.…”
Section: Spectral Variations Of Cdommentioning
confidence: 99%